The textbook as conversational partner - Bakker, Terri; Eskell-Blokland, Linda; Ruane, Ilse (University of the Free State, 2010)
Undergraduate teaching in psychology relies heavily on textbooks. Once the text- book has been selected, lecturers tend to relax. Modern textbooks include ready-made slides and test banks. All the information the student needs to know is thus packaged, illustrated, colourful and ready. This article questions whether learning is a mere transfer of the contents of the textbook to the student’s mind. It would be more benefical if academics could view knowledge and learning from a postmodern, social constructionist perspective. This would imply a view of learning as a conversation rather than a linear process. This article proposes to take the ‘text’ out of the textbook and to engage with it together with other texts such as tests, class material and conversations in a larger context.

Voorgraadse sielkunde-onderrig leun swaar op handboeke. Sodra die handboek voorgeskryf is, is dosente geneig om te ontspan. Moderne handboeke sluit klaargemaakte dia’s sowel as klaargemaakte toetsitembanke in. Al die inligting wat die student moet ken is dus verpak, geïllustreer, kleurvol en gereed. Hierdie artikel bevraagteken egter of die leerproses slegs bestaan uit die oordrag van inligting uit die handboek na die student se verstand. Dit mag meer nuttig wees indien akademici die leerproses beskou vanuit ’n postmoderne, sosiaal konstruktivistiese oogpunt. Dit impliseer dat leer as ’n gesprek eerder as ’n liniêre proses beskou word. Die artikel stel voor dat die handboek as teks tesame met ander tekste soos toetse, klasmateriaal en gesprekke, binne ’n groter konteks, gebruik word.
Keywords: Undergraduate teaching; Psychology; Prescribed textbooks; Psychology education; Tertiary education